2017
DOI: 10.1001/jamacardio.2017.2895
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention vs Coronary Artery Bypass Grafting in Patients With Left Main Coronary Artery Stenosis

Abstract: Percutaneous coronary intervention and CABG show comparable safety in patients with LMCA stenosis and low to intermediate-complexity coronary artery disease. However, repeat revascularization is more common after PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 44 publications
2
57
0
5
Order By: Relevance
“…148 A significant interaction with time is notable, providing early benefit for PCI in terms of MI and periinterventional stroke, which is subsequently offset by a higher risk of spontaneous MI during long-term follow-up. The need for repeat revascularization is higher with PCI than with CABG.…”
Section: Left Main Coronary Artery Diseasementioning
confidence: 99%
“…148 A significant interaction with time is notable, providing early benefit for PCI in terms of MI and periinterventional stroke, which is subsequently offset by a higher risk of spontaneous MI during long-term follow-up. The need for repeat revascularization is higher with PCI than with CABG.…”
Section: Left Main Coronary Artery Diseasementioning
confidence: 99%
“…In a meta-analysis of the 4 largest studies of LMCA revascularization with follow-up available at 3 to 5 years, incorporating data from the EXCEL and NOBLE trials, the hazard ratio (HR) for death, stroke, or MI with PCI compared with CABG was neutral (1.06) in a random-effects model (P = 0.60). 22 Based on individual patient data reconstruction, the Kaplan-Meier estimates of death, stroke, or MI at 5 years were 18.3% for PCI and 16.8% for CABG (P = 0.52). No statistically significant subgroup interaction for this combined outcome was noted across studies based on the generation of DES used for PCI (P for interaction = 0.25).…”
Section: Meta-analyses Of Percutaneous Coronary Intervention Vs Coromentioning
confidence: 96%
“…In patients undergoing revascularization of LMCA stenosis, the PCI and CABG techniques are associated with a comparable risk. Although surgical intervention in the LMCA occlusion is an important treatment modality, it has been shown that there is no significant difference in the long-term outcomes between the two techniques provided the patient and procedure selection is appropriate (3,4). Additionally, in the SYNTAX trial subgroup analysis for LMCA revascularization, there was no significant difference between the PCI and CABG groups for a year (5).…”
Section: Discussionmentioning
confidence: 99%